Pengaruh Kompos Kulit Buah Kakao dan Defoliasi terhadap Pertumbuhan dan Hasil Tanaman Okra (Abelmoschus esculentus L.) - Yusni Daniati; Erlida Ariani; Husna Yeti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Okra is a type of high nutritious vegetable which, if consumed regularly, can prevent various diseases. The elongated and widening okra leaves cause the leaves located under the shade and are not exposed to sunlight, so the lower leaves become photosynthate competitors between the lower leaves and the fruit. To fulfillment of nutrient needs of okra plants can utilize organic material in the form of cocoa pod waste which is processed into compost. The aim of this study was to determine the effect of interactions and the main factors of cocoa pod compost and defoliation and to obtain a dose combination of cocoa pod composts and the best defoliation on the growth and yield of okra plants. This research has been carried out at the University of Riau Faculty of Agriculture Research Station in May-August 2018 in the form of experiments with a 4x2 faction arranged according to CRD. The first factor was cocoa pod compost (K), namely: K0 = without Composted Cocoa pod, K1 = 4 ton.ha-1, K2 = 8 ton.ha-1 and K3 = 12 ton.ha-1. The second factor was defoliation (D), D = = without defoliation, D1 = defoliation. The results showed that the interaction of cocoa pod compost and defoliation had significant effect on the parameters of total fruit weight of plants and plant photosynthesis rates. The application of  cocoa pod compost has no significant effect on all parameters, while defoliation has a significant effect on the intensity of the light being continued.Keywords :Okra, Cocoa Pod Compost, Defoliation